Development and validation of a short form of the Comprehensive assessment of Acceptance and Commitment Therapy processes (CompACT-SF) - Morris, Jessica (2019)
Psychological flexibility is the purported mechanism of chance in Acceptance and Commitment Therapy (ACT), theoretically underpinned by the six processes which make up the ACT ‘hexaflex’ model. However, it has been suggested that the processes can be clustered into three dyadic processes, namely ‘Openness to Experience’, ‘Valued Action’, and ‘Behavioural Awareness’.